2008
DOI: 10.1016/j.chc.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Exposure Therapy for the Treatment of Traumatized Children and Adolescents (KidNET): From Neurocognitive Theory to Field Intervention

Abstract: Many children in war-affected and refugee populations have experienced multiple traumatic experiences, and high rates of psychologic disorders, especially posttraumatic stress disorder (PTSD), are found. Intervention strategies require pragmatic and effective approaches to treatment. This article describes the rationale for and the use of narrative exposure therapy in children (KidNET). KidNET is a short-term treatment for PTSD based on a neurocognitive theory of traumatic memory. Early treatment trials, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 83 publications
1
73
0
9
Order By: Relevance
“…As a consequence, the association with danger spreads across contexts and even time as in a flashback. This forms the core of the pathological memory and behavior in PTSD (Elbert & Schauer, 2002;Elbert et al, 2006;Schauer et al, 2006;Neuner et al, 2008).…”
Section: The Concept Of a 'Trauma Network'mentioning
confidence: 98%
“…As a consequence, the association with danger spreads across contexts and even time as in a flashback. This forms the core of the pathological memory and behavior in PTSD (Elbert & Schauer, 2002;Elbert et al, 2006;Schauer et al, 2006;Neuner et al, 2008).…”
Section: The Concept Of a 'Trauma Network'mentioning
confidence: 98%
“…Also, an adapted child treatment is available (KidNET). Case reports show that in children exposed to war trauma, KidNET produced a signifi cant reduction of PTSD symptoms and depression (Neuner et al, 2008;Onyut et al, 2005;Schauer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…146 Similarly, Rosenthal and colleagues 144 studied the effectiveness of a transcendental meditation (a form of mantra meditation) program in a sample of 7 veterans with PTSD (5 completed treatment) and reported significant improvements on CAPS scores as well as a quality of life measure. Another recent study compared the effectiveness of a meditation-relaxation program (including mantra repetition and breathing exercises) to a validated narrative exposure therapy for children (KIDNET) 149 among children with probable PTSD (all criteria except duration met) following exposure to a tsunami. 145 The authors reported 100% participant retention and equivalent reductions in PTSD symptoms immediately posttreatment and at 6-month follow-up, with large effect sizes for both treatment modalities as well as improvements in functional outcomes (e.g., self-reported school performance).…”
Section: Additional Mindfulness-based Approaches For Ptsdmentioning
confidence: 99%